The effect of service quality and customer value on customer satisfaction and customer loyalty in Bank Sultra - Abdul Razak; Abdul hakim; Asraf Yunus (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The purpose of this study was to determine and analyze the effect of service quality and customer value on satisfaction and loyalty, the effect of satisfaction on loyalty, the role of satisfaction in mediating the relationship between service quality and customer value on customer loyalty in Bank Sultra. Analysis of data processing using the Structural Equation Model (SEM) with Lisrel software The results of the study found that service quality, customer value had a positive but insignificant effect on customer satisfaction but a positive and significant effect on customer loyalty. In addition, satisfaction has an effect on customer loyalty, and satisfaction itself could play a role in mediating the relationship between service quality and customer loyalty. In connection with these findings, researchers suggest the need to build and maintain customer loyalty with a strategy to increase factors that are considered not optimal by customers, such as reliability, responsiveness, assurance, and empathy, in addition to the need to maintain and develop a high sense of belonging to Bank Sultra customers by trying to emphasize to staff the importance of building emotional relationships with customers by greeting in a friendly manner, serving politely, interacting, and trying to understand the identity of the customer's background so that intimacy with customers is established.